2020
DOI: 10.1002/nafm.10436
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Ecology of Age‐0 Gar at Texoma Reservoir Inferred from Analysis of Stable Isotopes

Abstract: Conservation and restoration of gar (Lepisosteidae) populations in North America are increasingly of interest to fisheries managers. Alligator Gar Atractosteus spatula are being stocked as age‐0 fish in efforts to re‐establish extirpated populations. However, gars are known to be highly cannibalistic in hatcheries, suggesting that age‐0 Alligator Gar introduced into natural habitats may face predation pressures from other gar species, limiting the likelihood of released fish recruiting to the population. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…[842] found that stocked grass carp had to be greater than 450 mm in size to ensure they were not eliminated via largemouth bass predation. In Texoma Reservoir (Oklahoma and Texas, USA), grass carp occurred in 33.3% to 38.7% of the stomach content samples of juveniles of four gar species: alligator gar (Atractosteus spatula), longnose gar (Lepisosteus osseus), shortnose gar (Lepisosteus platostomus), and spotted gar (Lepisosteus oculatus) [843]. The size of the grass carp consumed by gar in this study are not directly reported, but the grass carp sampled from the Texoma Reservoir for additional gar diet analyses had 42 to 98 mm total length, whereas the mean lengths of the gar species sampled ranged from 135 mm (shortnose gar) to 194 mm (longnose gar) total length, suggesting that only small juvenile grass carp are susceptible to predation by juvenile gar.…”
Section: Biological Control Predatorsmentioning
confidence: 99%
“…[842] found that stocked grass carp had to be greater than 450 mm in size to ensure they were not eliminated via largemouth bass predation. In Texoma Reservoir (Oklahoma and Texas, USA), grass carp occurred in 33.3% to 38.7% of the stomach content samples of juveniles of four gar species: alligator gar (Atractosteus spatula), longnose gar (Lepisosteus osseus), shortnose gar (Lepisosteus platostomus), and spotted gar (Lepisosteus oculatus) [843]. The size of the grass carp consumed by gar in this study are not directly reported, but the grass carp sampled from the Texoma Reservoir for additional gar diet analyses had 42 to 98 mm total length, whereas the mean lengths of the gar species sampled ranged from 135 mm (shortnose gar) to 194 mm (longnose gar) total length, suggesting that only small juvenile grass carp are susceptible to predation by juvenile gar.…”
Section: Biological Control Predatorsmentioning
confidence: 99%